Application of Digital Marketing in Developing Khao Garos Natural Tourism Potential in Krabi Thailand - Pattanapokinsakul, Kanyapat; Sarwono, Aldi Wisnumurti; Laurence, Jessicha (International Journal Of Tourism, 2023)
Khao Garos nature tourism is one of the tourism potentials in Nai Nang village, a Community Based Tourism village in Krabi Province, Thailand. Khao Garos offers natural tourist attractions going along the river on a long tail boat while enjoying the beauty of the limestone mountain range. Apart from that, Khao Garos natural tourist attraction also offers kayaking experiences, which add the value to this tourist attraction. However, Khao Garos tourism still has some weaknesses, among them are the lack of information regarding its natural tourism potentials and also its marketing. This study tries to answer the question of why digital marketing should be applied to Khao Garos tourist destination, and how to implement the digital marketing. The method used is descriptive qualitative using primary data in the form of observations and interviews, as well as secondary data in the form of literature and document studies related to Khao Garos tourism. The results show that digital marketing can provide more complete information about the natural tourism potentials of Khao Garos to potential tourists. Besides that, digital marketing can attract tourists to visit Khao Garos. Meanwhile, the application of digital marketing that can be done is through creating an informative website and through various social media platforms such as: Facebook, Instagram and TikTok